Análise do potencial solar térmico em um segmento do setor de alimentos e bebidas na Paraíba - Melquíades, Thiago Freire (2016)
Solar energy is the most abundant energy source in the Earth, however, still little explored by modern society, compared to another sources. This dissertation analyzed the potential use of solar thermal collectors in the food and beverage’ industry segment in Paraíba. And specifically analyzed through regional indicators, the relevance of potential segments of food and beverages from Paraiba for the use of Solar Heating Systems (SAS). It was also analyzed the technical and economic feasibility of using solar thermal collectors in a in a manufacturing company of ice cream and other ices, located in João Pessoa. It was found through the environmental impacts Life Cycle Assessment associated with the pasteurization process in an ice cream manufacturing company and other ices in Joao Pessoa, comparing the replacement of atmospheric burner LPG (Liquefied Petroleum Gas) to Solar Heating System. It was analyzed the Global Solar Radiation Series, from July 2007 to December 2013 in the city of Joao Pessoa Paraiba, using the ARIMA family models and testing the models estimated in 2014 forecast. The methodologies used were: regional analysis, through location and regional measures, life cycle assessment using the IPCC 2013 GWP 100a method, the Box and Jenkins method of time series analysis; and technical and economic analysis through NBR 15569 and financial indicators. The main results were: the sub-sectors of the food industry are distributed similarly between mesoregions. The SAS provided smaller environmental impact as compared to atmospheric burner. The SARIMA model (2,1,0) (2,1,3) 12 was the one that provided the best fit global solar radiation for 2014. It was concluded that the use of solar thermal collectors in the segment of the food and beverage industry in Paraíba is feasible according points of view technical, economic and environmental.